2015
DOI: 10.1038/ncomms7207
|View full text |Cite
|
Sign up to set email alerts
|

Carbon–carbon bond activation of cyclobutenones enabled by the addition of chiral organocatalyst to ketone

Abstract: The activation of carbon–carbon (C–C) bonds is an effective strategy in building functional molecules. The C–C bond activation is typically accomplished via metal catalysis, with which high levels of enantioselectivity are difficult to achieve due to high reactivity of metal catalysts and the metal-bound intermediates. It remains largely unexplored to use organocatalysis for C–C bond activation. Here we describe an organocatalytic activation of C–C bonds through the addition of an NHC to a ketone moiety that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(37 citation statements)
references
References 78 publications
0
36
0
1
Order By: Relevance
“…Elegant work by Chi and coworkers, involving an organocatalyst-promoted ring-opening of cyclobutenones followed by a formal enantioselective hetero-Diels-Alder reaction with sulfonyl and isatin imines, represents the closest example. 5 Given the importance of optically enriched lactam moieties in bioactive compounds, 6 herein a Rh-catalyzed enantioselective intramolecular carboacylation of oximes (imines) is described via C–C activation of benzocylcobutenones 7,8,9 to access chiral fused lactams (Scheme 1B). Considering the prevalence of hydroisoquinolines and isoquinolinones in natural products and pharmaceuticals, 10 this method also provides a unique entry to these scaffolds (Scheme 1C).…”
Section: Introductionmentioning
confidence: 99%
“…Elegant work by Chi and coworkers, involving an organocatalyst-promoted ring-opening of cyclobutenones followed by a formal enantioselective hetero-Diels-Alder reaction with sulfonyl and isatin imines, represents the closest example. 5 Given the importance of optically enriched lactam moieties in bioactive compounds, 6 herein a Rh-catalyzed enantioselective intramolecular carboacylation of oximes (imines) is described via C–C activation of benzocylcobutenones 7,8,9 to access chiral fused lactams (Scheme 1B). Considering the prevalence of hydroisoquinolines and isoquinolinones in natural products and pharmaceuticals, 10 this method also provides a unique entry to these scaffolds (Scheme 1C).…”
Section: Introductionmentioning
confidence: 99%
“…Later, Chi and co‐workers also developed a formal [3+2] cycloaddition between 4‐chlorocyclobutenones 118 and azomethine imines catalyzed by a chiral isothiourea catalyst 119 (Scheme ) . Unlike their earlier work, upon 1,2‐addition and ring opening, the α‐carbon of the enolate intermediate 120 , instead of the γ‐carbon, attacked the azomethine imines and eventually provided heterocycle 121 . A variety of functional groups were well tolerated, giving high diastereo‐ and enantioselectivity, although bulky substrates lowered both the yields and enantioselectivities.…”
Section: Nucleophile‐induced Ring Openingmentioning
confidence: 99%
“…Such a formal [4+2] cycloaddition with cyclobutenones can also be realized with N‐heterocyclic carbene (NHC) catalysts. In 2015, Chi and co‐workers reported that a chiral NHC carbene (e.g., 115 ) catalyst effectively coupled imines 111 with cyclobutenones 112 in good yield and high enantioselectivity (Scheme ) . As proposed, the enolate intermediate 113 , formed after the 1,2‐addition and concomitant ring opening, underwent a stepwise addition with imines to give lactam 114 , bearing a quaternary carbon center as a single diastereomer.…”
Section: Nucleophile‐induced Ring Openingmentioning
confidence: 99%
“…Furthermore, the cyclobutenedione ring can be further transformed by thermolysis [80], photolysis [81] and the application of organocatalysts [82] to generate highly functionalized compounds.…”
Section: Z-enolatementioning
confidence: 99%